(untitled) (Prilozi za orijentalnu filologiju, 2017)
The paper offers a contrastive analysis of prepositions in Persian and Bosnian language. The prepositions were analyzed with respect to their definitions, positions, classifications, meanings and uses. The classification of prepositions in Bosnian was used as a framework for their classification in Persian. The prepositions were thus, with respect to their origin, divided into original (true) and derived (prepositional expressions). Based on analysis of prepositions in the two languages, certain similarities and differences were established. Central to this paper is the Persian preposition [äz]. Its main meanings in Persian were analyzed, and examples for each individual meaning quoted from the selected corpus. At the same time, Bosnian translational equivalents of this preposition were presented.